ECOLOGY OF CRIME AND ECOLOGICAL EXPLANATIONS IN CRIMINOLOGY (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2022)
The delinquent area, as the basic concept of ecological theory in criminology,is a natural area that exists in the city, such as ghettos, which ariseс in the processof urbanization and development and is significant for its characteristic patterns ofantisocial behavior. The concept of a delinquent area comes directly from the conceptof a natural area in environmental theory, and the epithet “delinquent” refers to thedominant pattern of behavior expressed by a large number of residents in that area.The theory of crime prevention, through the appearance of the environment, is basedon the simple idea that the crime partly originates from the circumstances that arein the physical environment. Some of the research in the field of victimology wasdevoted to examining the impact that a ‘satisfactory’ neighborhood would haveon victimization and social participation of the population, and ultimately on theexperience of security in the neighborhood. It is emphasized that such an approachpresupposes systematic testing of the relative importance of victimization, theimportance of the quality of the neighborhood environment and social integrationwithin society in preventing the fear of crime. The observation of child abuse in thedelinquent area, related to the unity of the environment-sociology-culture model, isfocused on the experience of stress in society, which is considered to be the primarycause of victimization. This category of abuse includes the following causes: stressenvironment model; social learning model; socio-psychological model and the model of psychosocial systems.